2010
DOI: 10.1007/s10165-009-0270-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-neutrophil cytoplasmic autoantibodies against bactericidal/permeability-increasing protein in patients with rheumatoid arthritis and their correlation with bronchial involvement

Abstract: Anti-neutrophil cytoplasmic autoantibodies against bactericidal/permeability-increasing protein (BPI-ANCA) are known to be present in patients with cystic fibrosis, diffuse panbronchiolitis, and inflammatory bowel disease, especially in relation to chronic Gram-negative bacterial infection. To investigate the possible role of BPI-ANCA in rheumatoid arthritis (RA), we measured the serum titer of BPI-ANCA and examined clinical manifestations, including pulmonary complications, in patients with RA. Seventy-four R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…CX3CR1 [666], CD177 [690], PF4 [691], FFAR2 [692], MPO (myeloperoxidase) [693], F11 [694], S100A8 [695], VEGFD (vascular endothelial growth factor D) [674], IL1A [696], BPI (bactericidal permeability increasing protein) [697], AQP4 [698], BDNF (brain derived neurotrophic factor) [699], CXCL10 [700], RNASE2 [701], FCGR3B [702], S100A9 [703], IL1B [704], CXCR2 [705], GPIHBP1 [294], CD36 [706], TRIB3 [707], PCSK9 [708], FGF2 [709], FASN (fatty acid synthase) [710], PNPLA3 [711], HSPA6 [712], VIP (vasoactive intestinal peptide) [713], TLR3 [683], ADRB1 [328], SPOCK2 [714], TLR8 [715], CCR2 [716], IFIT3 [717], NEK7 [718], TLR7 [687], EFNB2 [719], CAV1 [720], CR1 [721] and AQP5 [722] plays essential roles in viral respiratory diseases. Previous study confirmed that CX3CR1 [723], S100A12 [724], CD177 [725], PF4 [726], MPO (myeloperoxidase) [727], CD5L [728], F11 [729], S100A8 [730], PGLYRP1 [731], GPR15 [732], BPI (bactericidal permeability increasing protein) [733], AQP4 [734], BDNF (brain derived neurotrophic factor) [735], CXCL10 [736], FCGR3B [737], S100A9 [738], IL1B [739], CXCR1 [740], CXCR2 [741], AFF3 [742], WNT3A [743], FCN3 [744], AZGP1 [745], CD36 [746], PCSK9 [747], GPX3 [748], FGF2 [749], SHH (sonic hedgehog signaling molecule) [750], SLC7A11 [751], VIP (vasoactive intestinal peptide) [752], KL (klotho) [753], APOA1 [754], RASGRF1 [75...…”
Section: Discussionmentioning
confidence: 74%
“…CX3CR1 [666], CD177 [690], PF4 [691], FFAR2 [692], MPO (myeloperoxidase) [693], F11 [694], S100A8 [695], VEGFD (vascular endothelial growth factor D) [674], IL1A [696], BPI (bactericidal permeability increasing protein) [697], AQP4 [698], BDNF (brain derived neurotrophic factor) [699], CXCL10 [700], RNASE2 [701], FCGR3B [702], S100A9 [703], IL1B [704], CXCR2 [705], GPIHBP1 [294], CD36 [706], TRIB3 [707], PCSK9 [708], FGF2 [709], FASN (fatty acid synthase) [710], PNPLA3 [711], HSPA6 [712], VIP (vasoactive intestinal peptide) [713], TLR3 [683], ADRB1 [328], SPOCK2 [714], TLR8 [715], CCR2 [716], IFIT3 [717], NEK7 [718], TLR7 [687], EFNB2 [719], CAV1 [720], CR1 [721] and AQP5 [722] plays essential roles in viral respiratory diseases. Previous study confirmed that CX3CR1 [723], S100A12 [724], CD177 [725], PF4 [726], MPO (myeloperoxidase) [727], CD5L [728], F11 [729], S100A8 [730], PGLYRP1 [731], GPR15 [732], BPI (bactericidal permeability increasing protein) [733], AQP4 [734], BDNF (brain derived neurotrophic factor) [735], CXCL10 [736], FCGR3B [737], S100A9 [738], IL1B [739], CXCR1 [740], CXCR2 [741], AFF3 [742], WNT3A [743], FCN3 [744], AZGP1 [745], CD36 [746], PCSK9 [747], GPX3 [748], FGF2 [749], SHH (sonic hedgehog signaling molecule) [750], SLC7A11 [751], VIP (vasoactive intestinal peptide) [752], KL (klotho) [753], APOA1 [754], RASGRF1 [75...…”
Section: Discussionmentioning
confidence: 74%
“…There was no difference in concentrations of IgG anti-MAA antibody (P = 0.09). ANCAs (92) Single unadjusted study found no difference in titers of BPI-ANCA (P = 0.09), cytoplasmic-ANCA (P = 0.98), or perinuclear-ANCA (P = 0.08) between RA-ILD and RA bronchial diseases. RF (46,78,92) Two studies found no difference in RF titer/concentration between RA-ILD and RA airway disease (mean concentration/titer 208.…”
Section: Biomarker (Citation) Outcomementioning
confidence: 84%
“…ANCAs (92) Single unadjusted study found no difference in titers of BPI-ANCA (P = 0.09), cytoplasmic-ANCA (P = 0.98), or perinuclear-ANCA (P = 0.08) between RA-ILD and RA bronchial diseases. RF (46,78,92) Two studies found no difference in RF titer/concentration between RA-ILD and RA airway disease (mean concentration/titer 208. Three studies with unadjusted analyses, one finding higher levels of KL-6 in RA-ILD compared with RA airway disease (mean concentration/titer 646 [RA-ILD] vs. 394.3 U/ml [RA airway disease], P = 0.018).…”
Section: Biomarker (Citation) Outcomementioning
confidence: 84%
“…This topic will be discussed in the section on pathogenesis. (b) Clinical studies suggest that formation of ANCA in several conditions considered noninfectious, such as sclerosing cholangitis, autoimmune hepatitis, inflammatory bowel disease [23], and rheumatoid arthritis [24] is triggered by secondary infections. …”
Section: Anca Formation During the Course Of Various Illnessesmentioning
confidence: 99%